2020
DOI: 10.1021/acs.jchemed.0c01166
|View full text |Cite
|
Sign up to set email alerts
|

Some Like It Hot: Experimentally Determining ΔΔH, ΔΔS, and ΔΔG between Kinetic and Thermodynamic Diels–Alder Pathways Using Microwave-Assisted Synthesis

Abstract: The effects of kinetic vs thermodynamic control on endo/exo stereoisomer ratios can be observed in a simple Diels−Alder reaction between Nphenylmaleimide and furan. The use of microwave-promoted synthesis affords the cycloadducts in yields ranging from 65−100%, employing reaction times of 1−10 min at temperatures of 55−130 °C. Short reaction times enable screening of numerous reaction conditions (time and temperature) within a single lab period, where endo:exo product ratios follow the primary facets of kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…− capturing the hydrogen atom on the newly substituted carbon atom leads to final products 3 and 4. 3,5…”
Section: ■ Considering the Intermolecular Friedel−crafts Alkylation R...mentioning
confidence: 99%
See 3 more Smart Citations
“…− capturing the hydrogen atom on the newly substituted carbon atom leads to final products 3 and 4. 3,5…”
Section: ■ Considering the Intermolecular Friedel−crafts Alkylation R...mentioning
confidence: 99%
“…Next, M1 and M1* undergo the electrophilic aromatic substitution process with rate constants k 1 and k 2 to give the intermediates M2 and M2* , respectively. Subsequent deprotonation via AlCl 4 – capturing the hydrogen atom on the newly substituted carbon atom leads to final products 3 and 4 . , …”
Section: Considering the Intermolecular Friedel–crafts Alkylation Rea...mentioning
confidence: 99%
See 2 more Smart Citations
“…One such factorstereochemistry of DA adductsstems from the two isomers, endo and exo derivatives, dissociating at significantly different temperatures. , Previously, we demonstrated that selective dissociation of endo and exo DA adducts occurs in solvent-free networks and the conversion between endo and exo adducts through thermal annealing can be used to efficiently reconfigure the permanent shape of such polymer networks. Although the stereochemistry of the DA reaction is documented for reactions in dilute solutions of low-molecular-weight compounds, , a clear understanding for solvent-free polymer networks is lacking. Reactions involving polymer chains are associated with conformational entropy changes , and the entropic effects of the crosslinking network on DA reaction are expected to be significant.…”
Section: Introductionmentioning
confidence: 99%